Analysis Of Factors Related To Stunting Prevention In Children Aged 2-5 Years - Yuliasti Eka Purnamaningrum; Kirana Dewi Pertiwi; Margono Margono; Denny Iswara (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: Nutritional status in Indonesia, especially stunting in toddlers, is still a problem that is influenced by many interrelated factors. This Study aimed to analyze the factors related to prevention of stunting in toddlers. Methods: This study used a cross-sectional design. The population was 131 mothers who have children aged 2-5 years at Timbulharjo village, Sewon, Bantul with number of samples are 57 people using purposive sampling technique. The independent variables were prior related behavior, education level, socio-economic status, perceived benefits to action and perceived barrier to action. Dependent variable was prevention of stunting. Data were collected using questionnaire and analyzed using logistic regression with a significance level α 0.05. Results: The vast majority (54.4%) of maternal education is high school (61.4%) with a family income of <1,790,500, most respondents have the benefit of perceived actions insufficient categories (56.1%). High prior related behavior was 1.26 times better at stunting prevention than low prior related behavior. Any change per 1 unit on the previous behavioral variable and a change per 1 unit on the benefit variable of the perceived action, will increase the likelihood of stunting prevention behavior (4.6%). Conclusion: Factors associated with stunting prevention behavior are prior related behavior and perceived benefit to action. The dominants factor related to stunting prevention behavior is prior related behavior. This research showed that it is able to add information and improve stunting prevention behavior for the community. This can be realized through collaboration with health workers to conduct integrated service program held an activities, training, workshop, and family mentoring related to stunting prevention.